Perlindungan Hak Cipta Penerbit Terhadap Buku Ciptaan Yang Telah Menjadi Public Domain - Muh. Aldhyansah Dodhy Putra (Fakultas Hukum Universitas Islam Indonesia, 2020)
AbstractAct Number 28 of 2014 on Copyright regulates changes in the period of protection of a work. One of them is about books, which were previously protected 50 years after the author's death was amended to 70 years after the author's death in Article 58 (1) of Act Number 28 of 2014 on Copyright. This change not only has implications for increasing the length of time to protect many of the late author's works but also creates new confusion regarding the status of authors who have died more than 50 years before the enactment of the law. This regulatory change has led to research on the protections that publishers have for books with expired protection period (public domain). The method used in this research is juridical-normative research, which examines several regulations, especially Act Number 28 of 2014 on Copyright. The results show that publishers can obtain copyright protection for public domain books as long as they do not violate moral rights and that there are common misconceptions regarding the length of time for book copyright protection due to regulation changes.Keywords: Copyright, Public Domain, Publisher